In‐situ force measurement during nano‐indentation combined with Laue microdiffraction. Issue 1 (21st October 2020) - Lauraux, Florian; Yehya, Sarah; Labat, Stéphane; Micha, Jean‐Sébastien; Robach, Odile; Kovalenko, Oleg; Rabkin, Eugen; Thomas, Olivier; Cornelius, Thomas W.
Abstract: For the characterization of the mechanical properties of materials the precise measurements of stress‐strain curves is indispensable. In situ nano‐mechanical testing setups, however, may lack the precision either in terms of strain or stress determination. Recently, the custom‐built scanning force microscope SFINX was developed which is compatible with third‐generation synchrotron end‐stations allowing for in situ nano‐mechanical tests in combination with nanofocused synchrotron x‐ray diffraction that is highly sensitive to strain and defects. The usage of a self‐actuating and self‐sensing cantilever tremendously increases the compactness of the system but lacks deflection sensitivity and, thus the force measurement. This deficiency is resolved by in situ monitoring the diffraction peaks of the Si cantilever by Laue microdiffraction during the nano‐indentation of a gold crystal. The orientation and, hence, the deflection of the Si cantilever is deduced from the displacement of the Si Laue spots on the detector giving force accuracies of better than 90 nN. At the same time, the dislocation density in the indented Au crystal is tracked by monitoring the Au Laue spots eventually resulting in complete stress‐dislocation density curves. Abstract : The precise measurement of both stress and strain is indispensable for the accurate characterization of mechanical properties, which is however difficult in crowded environments. Here, the force measurement with a resolution of 90 nN is realized by in situ monitoring the AFM cantilever deflection by Laue microdiffraction during nano‐indentation and simultaneously measuring the dislocation density in the indented gold crystal.